A study on factors affecting the implementation of industrialized building system (IBS) on high-rise construction in developing regions of Malaysia - Lim, Chun Fee; Sam, Man Keong (INTI International University, 2018)
The objectives of this paper are to investigate the suitability of IBS and to propose a new framework to improve IBS on high-rise construction project in undeveloped area of Malaysia. Data were collected through online questionnaire from G7 contractors (Central Region and East Coast). The results showed that reduction in construction duration is the main factor affecting the implementation of IBS in Central Region whilst capability and capacity to implement IBS is the main problem in East Coast region. Government support is needed to the successful implementation of IBS.